TBLT Task and Framework: Insights from Indonesian Context - Doris Sukma (Journal of English Language Teaching, Literature and Culture, 2024)
This study employs a document study to investigate the tasks and TBLT framework used in Indonesian English classrooms < em>Through a rigorous examination of existing literature and empirical research this study will elucidate how these practices contribute to the development of communicative competence a core tenet of the Merdeka Curriculum< em> < em>Several recent studies past five years on TBLT practices have been identified through a review of open access journals < em>The findings reveal a prevalence of authentic tasks consistent with expert recommendations but with varying levels of authenticity In addition implementing TBLT generally aligns with established principles particularly those proposed by Willis but only a few adaptations are made to suit local teaching and learning goals While these findings suggest a positive trend further analysis is needed to identify potential areas for improvement and inform future TBLT practices in Indonesian classrooms < em>< p>